Evaluating a business model for vehicle-grid integration: Evidence from Germany. (January 2017) - Brandt, Tobias; Wagner, Sebastian; Neumann, Dirk
Highlights: We model a business case for using electric vehicles to provide frequency control. Business model is evaluated using an extensive data set for Germany. Results show that frequency regulation is not profitable with current energy prices. Viability of electric fleets to support grid stability may be overestimated. Political efforts to reform energy market design are encouraged. Abstract: Intelligently managing the charging processes of electric vehicles is generally considered to be a promising method of supporting the integration of volatile renewable energy sources into the power grid. We analyze this concept from an economic perspective by developing and evaluating a business model for vehicle-grid integration. Specifically, we investigate the case of parking garage operators using the electric vehicles located at their facilities to provide reserve energy for frequency regulation. We evaluate revenues and cost structures using extensive real-world data sets on the German market for frequency regulation, on battery states of charge at different times of day, and on occupancy rates of parking facilities. We find that possible revenues, given current market conditions, are inferior to investment costs for charging and IT infrastructure. Even if the operator installs these features to enable customers to charge their vehicles for a fee, it would be more profitable to focus on this service and charge batteries immediately when the vehicles enter the garage instead of delaying charging for frequency regulation. Overall, our results illustrate that studies on the relationship between electric vehicles and the integration of renewable energy sources require a closer look at the associated business models to derive robust economic and policy implications.